Pengaruh Relaksasi Pernafasan Terhadap Intesitas Nyeri Pada Persalinan Kala 1 Fase Aktif Di RS Pku Muhammadiyah Temanggung - Ery Kurnia; Andri Nur Sholihah (CV. ITTC INDONESIA, 2025)
One of the causes of pain during the first stage of labor in the active phase is contraction of the uterine muscles, hypoxia of the contracting muscles, stretching of the cervix when it opens, ischemia of the uterine corpus, and stretching of the lower uterine segment. Objective: To determine the effect of breathing relaxation techniques on reducing active phase I labor pain at PKU Muhammadiyah Temanggung Hospital. This research uses a pre-experimental research method with a one group pretest posttest research design. Samples were taken using a purposive sampling technique, namely 20 mothers giving birth. The instrument used in this research was the SOP (Standard Operating Procedure) sheet. Data were analyzed using the Wilcoxon Signed Ranks test. Before the Respiratory Relaxation Technique was carried out, the majority of respondents were on a scale of 7-9 (Severe Pain) as many as 11 people (55.0%). After using the Deep Breathing Technique, the majority of respondents were on a scale of 4-6 (Moderate Pain) as many as 17 people (85.0%). The Wilcoxon test results obtained a p value = 0.001. Thus, the p value is smaller than 0.05, so it can be concluded that there is an influence of the Relaxation Breathing Technique on the intensity of labor pain in the first active stage. There is an influence of the Respiratory Relaxation Technique on reducing labor pain in the active phase I of labor at the PKU Muhammadiyah Temanggung Hospital. It is hoped that mothers in labor can use Deep Breathing Relaxation Techniques to reduce pain effectively.